Safety of direct oral anticoagulants in patients with advanced liver disease. (10th July 2021) - Semmler, Georg; Pomej, Katharina; Bauer, David J. M.; Balcar, Lorenz; Simbrunner, Benedikt; Binter, Teresa; Hartl, Lukas; Becker, Jeannette; Pinter, Matthias; Quehenberger, Peter; Trauner, Michael; Mandorfer, Mattias; et al.
Abstract: Background & Aims: While direct oral anticoagulants (DOACs) are increasingly used in patients with liver disease, safety data especially in advanced chronic liver disease (ACLD) are limited. Methods: Liver disease patients receiving DOAC treatment (ACLD: n = 104; vascular liver disease: n = 29) or vitamin K antagonists (VKA)/low‐molecular‐weight heparin (LMWH; ACLD: n = 45; vascular: n = 13) between January 2010 and September 2020 were retrospectively included. Invasive procedures and bleeding events were recorded. Calibrated anti‐Xa peak levels and thrombomodulin‐modified thrombin generation assays (TM‐TGAs) were measured in a subgroup of 35/28 DOAC patients. Results: Among patients receiving DOAC, 55 (41.3%) had advanced liver dysfunction (Child‐Pugh‐stage [CPS] B/C) and 66 (49.6%) had experienced decompensation. Overall, 205 procedures were performed in 60 patients and procedure‐related bleedings occurred in 7 (11.7%) patients. Additionally, 38 (28.6%) patients experienced spontaneous (15 minor, 23 major) bleedings during a median follow‐up of 10.5 (IQR: 4.0‐27.8) months. Spontaneous bleedings in ACLD patients were more common in CPS‐B/C (at 12 months: 36.9% vs CPS‐A: 15.9%, subdistribution hazard ratio [SHR]: 3.23 [95% CI: 1.59‐6.58], P  < .001), as were major bleedings (at 12 months: 22.0% vs 5.0%, SHR: 5.82 [95% CI: 2.00‐16.90], P  < .001). Importantly, CPS (adjusted SHR: 4.12 [91% CI: 1.82‐9.37], P  < .001), but not the presence of hepatocellular carcinoma or varices, was independently associated with major bleeding during DOAC treatment. Additionally, ACLD patients experiencing bleeding had worse overall survival (at 12 months: 88.9% vs 95.0% without bleeding; P  < .001). Edoxaban anti‐Xa peak levels were higher in patients with CPS‐B/C (345 [95% CI: 169‐395] vs CPS‐A: 137 [95% CI: 96‐248] ng/mL, P  = .048) and were associated with lower TM‐TGA. Importantly, spontaneous bleeding rates were comparable to VKA/LMWH patients. Conclusions: Anticoagulants including DOACs should be used with caution in patients with advanced liver disease due to a significant rate of spontaneous bleeding events.